Impact of systematic improvement in jamun (Syzygium cuminii Skeels) cultivars on yield and quality of fruits (IASH Indian Journal of Arid Horticulture, 2024)
Jamun (Syzygium cumini) is a promising fruit crop for cultivation in central Gujarat due to its high adaptability to diverse environmental conditions and appreciable fruit yield. The genetic diversity and climate factors can influence tree growth, yield and quality attributes of jamun. This study aimed to assess the effects of genotype and year effect on the performance of four cultivars of jamun under rainfed conditions in central Gujarat (India). Experiments were carried out during 2020–2021 and 2021–2022. The experimental design was a randomized block design with three replications. Results revealed that the tree growth, fruit yield and fruit quality parameters were significantly affected by genotype while the year had a significant effect on plant growth characters only. In general, CISHJ-37 recorded the higher tree height, spread and stem girth over the years in comparison to other cultivars. However, fruit weight and pulp content were found stable over the years as not significantly affected by the year’s effect. Goma Priyanka and CISHJ-37 recorded the higher fruit and pulp weight while higher pulp (%) was recorded in CISHJ-42 during both the years. However, Goma Priyanka recorded significantly higher yield/tree during both the years followed by CISHJ-37 while least was observed in CISHJ-42. Similarly, higher TSS and acidity were recorded in Goma Priyanka and CISHJ-37 compared to Konkan Bahadoli. The “genotype” factor significantly affected fruit yield and quality attributes. The results indicate that, under rainfed conditions, high yielding improved cultivars like Goma Priyanka and CISHJ-37 can be profitable in central Gujarat.